Privilege or punish criminal justice and the challenge of family ties - Markel, Dan.; Collins, Jennifer M.; Leib, Ethan J. (Oxford : Oxford University Press, 2009)
This work answers two basic questions: how does the American criminal justice system address a defendant's family status? And how should a defendant's family status be recognized in a criminal justice system situated within a liberal democracy committed to egalitarian principles of non-discrimination?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of; Family violence -- Law and legislation; Punishment